Islamophobia beyond Explicit Hate Speech: Analyzing the Coverage of Muslims in Slovenia’s Public Broadcasting - Igor Jurekovič (Religions, 2024)
Religion in Europe has been undergoing two fundamental changes in the past four decades. As a side effect of secularization, religious fields have been pluralizing. On the other hand, religions themselves have taken a qualitative shift towards lived, material characteristics. Focusing exclusively on the diversification of European religious fields, we are interested in the concept of religious literacy as a tool for competent engagement in contemporary religious plural societies. To better understand the role of public media in fostering religious literacy, we offer an analysis of the public broadcaster’s coverage of smaller religious communities in Slovenia. Focusing particularly on Muslims as the largest religious minority in Slovenia, we provide an analysis of 245 episodes, consisting of 540 items, in the 2015–2020 period. We show that the coverage given to smaller religious communities is unevenly spread amongst the communities, with disproportional airtime given to Christian churches and communities. Furthermore, we pinpoint the key qualitative difference in portrayals of Slovenian Muslims and non-Catholic Christians, explaining how the process of racialized Islamophobia may continue beyond explicit hate speech. In conclusion we set out limitations of our study and provide guidelines for future research.